Avaliação do nível de selênio no leite humano cru e pasteurizado - Ribeiro, Elane Cristina Vallim (2017)
Selenium is an essential element found in human milk promotes wide antioxidant defense, exerts anti-inflammatory and cardiometabolic effects, becoming important in normal and fundamental physiology in situations of severe injury. It is now recognized that selenium, when offered to infants, especially critical and premature neonates at levels sufficient to ensure full function, contributes to reducing oxidative stress and its complications. Objective: To compare the total content of selenium in raw mature human milk before and after its pasteurization. Methods: A quantitative study composed of six healthy adult lactating women, who had full term deliveries, mother and healthy concept and did not make use of vitamin supplements. The aliquot of milk donated for dosing was obtained by manual extraction of 29th (± 3.6) days of lactation. To avaluate the total of selenium in human milk, the cathodics tripping voltammetry with differential pulse technique was performed, with a mercury pendant drop electrode with the support of antioxidants, water and catalysts. Results: The mean concentration of total selenium in mature raw milk human was 8.31 (± 3.30) μg/kg and after pasteurization 8.58 (± 2.65) μg/kg. Conclusion: The total selenium content in the human milk of the infants who composed the sample did not decrease with pasteurization.